A study on application of Artificial Intelligence and its challenges in HR - Ranjitha S; Usha K (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Artificial Intelligence is replication of human intelligence where it thinks like a human. it is also known as Machine learning. Artificial intelligence in Human Resource creates an opportunity for an organization personnel to improve their working involvement. The effective implementation of artificial intelligence application is innovative technology development in the organization. The primary objective of this research paper is to study the application of artificial intelligence and to measure the impact of artificial intelligence in HR. Artificial intelligence in Human resource is innovative technique which can helps to handle the different kinds of activities easily namely recruiting, retaining and so on,. This paper will give overview of artificial intelligence application in HR and challenges which were facing by the organization for the its effective implementation by collecting the data both from primary source as well as secondary source and gives suggestion for the better performance of artificial intelligence in HR.